Human Resources, Employment and Development / The Problems of Developed Countries and the International Economy: Volume 3 - Hughes Helen; Weisbrog Burton (St Martin Press, 1983)
Human Resources and Employment in Developed Countries, Manpower Policy and the Labour Market, Labour Market Issues, Education and Human Resource Development, Labour Supply and Income Distribution and Demographic Change: Lifetime and Intergenerational Aspects, The International Economy and Employment, Migration, Trade and Employment, Transnational Corporations and Employment, Index.